Anorectal Mucosal Melanoma in the Era of Immune Checkpoint Inhibition: Should We Change Our Surgical Management Paradigm?. Issue 5 (May 2021) - Adileh, Mohammad; Yuval, Jonathan B.; Huang, Shan; Shoushtari, Alexander N.; Quezada-Diaz, Felipe; Pappou, Emmanouil P.; Weiser, Martin R.; Garcia-Aguilar, Julio; Smith, J. Joshua; Paty, Philip B.; Nash, Garrett M.
Abstract : BACKGROUND: The advent of immune checkpoint inhibition therapy has dramatically improved survival in patients with skin melanoma. Survival outcomes after resection of anorectal melanoma treated with immune checkpoint inhibition have not been reported. OBJECTIVE: This study aimed to compare survival outcomes following surgical resection of anorectal melanoma between patients who received immune checkpoint inhibition and patients who did not. DESIGN: This study is a retrospective analysis of data from a prospectively maintained database. SETTING: This study was conducted at a comprehensive cancer center. PATIENTS: Patients who underwent surgery for anorectal melanoma between 2006 and 2017 were included. They were stratified according to the use of immune checkpoint inhibition. MAIN OUTCOME MEASURES: The primary outcomes measured were overall and disease-specific survival. RESULTS: Of the 47 patients included in the analysis, 29 (62%) received immune checkpoint inhibition therapy. Twenty-two (76%) of the 29 patients received immune checkpoint inhibition after detection of metastasis or disease progression rather than in the neoadjuvant or adjuvant setting. Overall survival did not differ significantly between patients who received immune checkpoint inhibition therapy and patients who did not (median, 52 and 20 months; 5-year rate, 41% vs 35%; p = 0.25). Disease-specific survival also did not differ significantly. Our analysis did not identify any clinical or pathological features associated with response to immune checkpoint inhibition therapy or with survival. LIMITATIONS: This study was limited by its relatively small sample and retrospective design and by the heterogeneous treatment regimen in the immune checkpoint inhibition group. CONCLUSIONS: Immune checkpoint inhibition therapy by itself does not appear to improve survival in patients who undergo resection or excision of anorectal melanoma. Combinations of immune checkpoint inhibition with other therapeutic modalities warrant further investigation. See Video Abstract at http://links.lww.com/DCR/B499 . MELANOMA DE LA MUCOSA ANORRECTAL EN LA ERA DE LOS INHIBIDORES DEL PUNTO DE CONTROL INMUNOLÓGICO: ¿DEBEMOS DE CAMBIAR NUESTRO PARADIGMA DEL MANEJO QUIRÚRGICO: ANTECEDENTES: El advenimiento de la terapia de los inhibidores del punto de control inmunológico, han mejorado dramáticamente la supervivencia en pacientes con melanoma de piel. No se han informado los resultados de supervivencia después de la resección del melanoma anorrectal, tratado con inhibidores del punto de control inmunológico. OBJETIVO: Comparar los resultados de supervivencia después de la resección quirúrgica de melanoma anorrectal entre pacientes que recibieron y no recibieron inhibidores del punto de control inmunológico. DISEÑO: Análisis retrospectivo de una base de datos mantenida prospectivamente. AJUSTE: Centro oncológico integral. PACIENTES: Pacientes que se sometieron a cirugía por melanoma anorrectal entre 2006 y 2017. Los pacientes fueron estratificados según el uso de inhibidores del punto de control inmunológico. PRINCIPALES MEDIDAS DE RESULTADO: Supervivencia global y específica de la enfermedad. RESULTADOS: De los 47 pacientes incluidos en el análisis, 29 (62%) recibieron terapia de inhibidores del punto de control inmunológico. Veintidós (76%) de los 29 pacientes recibieron inhibidores del punto de control inmunológico después de la detección de metástasis o progresión de la enfermedad, en vez de administración adyuvante o neoadyuvante. La supervivencia global no varió significativamente entre los pacientes que recibieron o no recibieron terapia de inhibidores del punto de control inmunológico (mediana, 52 y 20 meses, respectivamente; tasa a 5 años, 41% frente a 35%, respectivamente; p = 0, 25). La supervivencia específica de la enfermedad tampoco varió significativamente. Nuestro análisis no identificó ninguna característica clínica o patológica, asociada con la respuesta a la terapia de inhibidores del punto de control inmunológico o con la supervivencia. LIMITACIONES: Muestra relativamente pequeña y diseño retrospectivo. Régimen de tratamiento heterogéneo en el grupo de inhibidores del punto de control inmunológico. CONCLUSIONES: La terapia por sí sola, de inhibidores del punto de control inmunológico, no parece mejorar la supervivencia en pacientes que se someten a resección o escisión de melanoma anorrectal. Las combinaciones de inhibidores del punto de control inmunológico con otras modalidades terapéuticas, merecen una mayor investigación. Consulte Video Resumen en http://links.lww.com/DCR/B499 . (Traducción—Dr. Fidel Ruiz Healy )